Trichophyton tonsurans: um patógeno emergente, análise clínica, laboratorial e homologia do DNA - Oliveira, Luciana Maria Pereira de (2004)
Background: Tinea capitis is a mycotic infection of the scalp, conunon in school-aged and pre-pubescent children, which occurs all over the world. It is caused by dermatophyte fungi of the genus Trichophyton or Microsporum. Trichophyton tonsurans is an anthropophylic fungus and is being considered an emerging pathogen in terms of the etiology of Tinea capitis. It catches the interest of researchers with social concerns due to its high incidence among low- income populations and its possible endemic behavior. Objectives: To evaluate the clinicai aspect of Tinea capitis with positive and negative cultures; to study the phenotypic characteristics of various stains that have been isolated in relation to the clinicai aspect and to analyze the profile of the genome from T. tonsurans strains using RAPD and correlate the fmdings. Methods: 76 patients with suspected Tinea capitis were treated, involving the scalp and body hair. The patients were analyzed. Clinicai samples were taken by scraping the scalp if the tonsure zone; the samples were examined directly under the microscope and identified in the laboratory through the macro and micromorphology of the colonies. Studies were made of enzymatic, physiological activity and nutritional requirements. Next 17 strains of T. tonsurans were selected and submitted to an analysis of their genetic profile through random amplified polymorphic DNA (RAPD), using the primers OPAO-15. The PCR products were visualized polyacrylamide gel followed by silver staining. Results: Of the suspected cases of Tinea capitis (76 patients), 40 patients (60.52%) were confirmed through a positive culture for dermatophyte. 35 (87.5%) of the 40 cases of Tinea Capitis, were of T. tonsurans. There was a greater prevalence among women. Of the 40 positive cultures, 26 (65%) were females. Regarding age, the greatest interval was in the 0-5 age group (40%). Of clinicai manifestations scaly dermatosis (85.7%), erythematous lesions (37.1%) and hair loss with or without black dot(57.1%) were the most conunon. In the RAPD analysis, were observed three distinct genetic perfile, with production different bands patterns from T. tonsurans strain literature. Conclusion: Females and a 0-5 age group were the most common, corroborating the argument that as it is anthropophylic T. tonsurans provoked little inflammatory reaction. T tonsurans has a high incidence in regions where living conditions, hygiene and other habits are precarious, reflecting the fact that this anthropophylic fungus is higlily contagious and that the pathogen is very well adapted to our climatic conditions. The T. tonsurans strain from this study are different, this represents a new species of dermatophyte, with a large morphological variation, atypical characteristics in its macromorphology (colonies with glabrous textures) and in the micromorphology (the presence of large quantities of chlamydoconids in primary isolation) further on this genotypical presentation, differing from the literature.